Positive electrode active material precursor, method for preparing positive electrode active material using same, and positive electrode active material
By using a composite transition metal positive electrode active material precursor in the form of a single particle in the lithium secondary battery and firing at low temperatures, the structural changes caused by high-temperature heat treatment are solved, and the performance and life of the battery are improved.
Patent Information
- Application Number
- CN202380037633.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-22
- Publication Date
- 2024-12-13
AI Technical Summary
During the high-temperature heat treatment of the positive electrode active material of the lithium secondary battery, the R-3m layered structure is not maintained, and lithium is released from the crystal structure, causing the phase to change into the Fm-3m rock salt structure, reducing the crystallinity of the positive electrode active material and affecting the battery. capacity and life characteristics.
A precursor of the positive electrode active material containing a composite transition metal in the form of a single particle is obtained by mixing with transition metal hydroxide and oxide and firing at a temperature of 700°C to below 830°C. Metal oxides maintain layered structure and improve crystallinity.
It is possible to obtain a positive electrode active material in the form of a single particle when firing at low temperatures, improve the capacity, life and resistance characteristics of the battery, and reduce gas production.
Smart Images

Figure CN119137072A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority from Korean Patent Application No. 10-2022-0062289 filed in the Korean Intellectual Property Office on May 20, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a positive electrode active material precursor, a method for preparing a positive electrode active material using the positive electrode active material precursor, and a positive electrode active material prepared by the method. Background Art
[0004] In recent years, with the technological development and increase in demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life, and low self-discharge rate have been commercialized and widely used.
[0005] As positive electrode active materials for lithium secondary batteries, lithium transition metal oxides have been developed, for example, lithium cobalt oxides such as LiCoO2, lithium nickel oxides such as LiNiO2, lithium manganese oxides such as LiMnO2 or LiMn2O4, lithium iron phosphate oxides such as LiFePO4, etc. In recent years, lithium composite transition metal oxides containing two or more transition metals, such as Li[Ni a Co b Mn c ]O2, Li[Ni a Co b Al c ]O2 and Li[Ni a Co b Mn c Al d ]O2.
[0006] The lithium transition metal oxides developed so far are generally prepared by the following steps: lithium transition metal hydroxide is prepared by a coprecipitation reaction by adding ammonia water as a chelating agent and a sodium hydroxide aqueous solution as an alkaline aqueous solution to a solvent in which a transition metal-containing raw material (such as nickel sulfate, cobalt sulfate, manganese sulfate, etc.) is mixed, and then the lithium transition metal hydroxide, the lithium-containing raw material and the selective raw material containing the doping element are mixed, and then a high-temperature heat treatment is performed.
[0007] When lithium transition metal hydroxide is prepared as described above, lithium transition metal hydroxide in the form of spherical secondary particles formed by agglomeration of primary particles of several nm to several tens of nm is formed as a positive electrode active material precursor, and in order to prepare a positive electrode active material in a single particle form, a high temperature heat treatment of 830° C. or above is required.
[0008] However, when a high temperature heat treatment of 830°C or more is performed to prepare a positive electrode active material in the form of a single particle, the layered structure of R-3m is not properly maintained, and lithium is released from the crystal structure, resulting in a phase transition to an Fm-3m rock salt structure such as NiO, thereby reducing the crystallinity of the positive electrode active material, so that there is a problem in that the capacity characteristics and life characteristics of a battery containing the positive electrode active material are reduced and the resistance increase rate is increased. On the other hand, when heat treatment is performed at a temperature lower than 830°C, there is a problem in that, in the case of a single particle, due to the presence of an over-fired secondary particle form, the effect of improving life and reducing gas generation does not reach the expected level.
[0009] Therefore, research has been conducted in an attempt to develop a cathode active material precursor that does not require high-temperature heat treatment of 830° C. or higher in order to increase the crystallinity of the cathode active material when preparing the cathode active material in the form of single particles. Summary of the invention
[0010] Technical issues
[0011] One aspect of the present invention provides a positive electrode active material precursor capable of realizing a positive electrode active material in a single particle form even when fired at a low temperature.
[0012] One aspect of the present invention also provides a method for preparing a positive electrode active material, which can obtain a positive electrode active material in a single particle form even when fired at a low temperature by using the positive electrode active material precursor in preparing the positive electrode active material.
[0013] Technical Solution
[0014] According to one aspect of the present invention, a positive electrode active material precursor, a method for preparing a positive electrode active material using the positive electrode active material precursor, and a positive electrode active material prepared by the method are provided.
[0015] (1) The present invention provides a positive electrode active material precursor, the positive electrode active material precursor comprising:
[0016] a first positive electrode active material precursor having a composition represented by the following Chemical Formula 1 and containing a composite transition metal in a single particle form, and
[0017] One or more selected from a second cathode active material precursor having a composition represented by Chemical Formula 2 below and a third cathode active material precursor having a composition represented by Chemical Formula 3 below.
[0018] [Chemical Formula 1]
[0019] Ni a1 M 1 b1 Mn c1 M 2 d1
[0020] In Chemical Formula 1 above,
[0021] M 1 is one or more selected from Co and Al,
[0022] M 2 is one or more selected from Nb, Ti, Mg, Ta, Zr, Ca, Mo, V, Y, W, and Sc, and
[0023] 0.6 ≤ a1 < 1, 0 < b1 ≤ 0.4, 0 ≤ c1 ≤ 0.4, 0 ≤ d1 ≤ 0.2, and
[0024] [Chemical Formula 2]
[0025] M 3 a2 M 4 b2 (OH) c2
[0026] In Chemical Formula 2 above,
[0027] M 3 is one or more selected from Ni, Co, Mn, Al, and Zr,
[0028] M 4 is one or more selected from Nb, Ti, Mg, Ta, Ca, Mo, V, Y, W, and Sc, and
[0029] 0 < a2 ≤ 1, 0 ≤ b2 < 1, 2 ≤ c2 ≤ 4, and
[0030] [Chemical Formula 3]
[0031] M 5 a3 M 6 b3 O c3
[0032] In Chemical Formula 3 above,
[0033] M 5is one or more selected from Ni, Co, Mn, Al and Zr,
[0034] M 6 is one or more selected from Nb, Ti, Mg, Ta, Ca, Mo, V, Y, W and Sc, and
[0035] 0 <a3≤3,0≤b3<3,1≤c3≤4。
[0036] (2) In the above (1), the present invention provides a positive electrode active material precursor, wherein the first positive electrode active material precursor has an average particle size (D 50 ).
[0037] (3) In the above (1) or (2), the present invention provides a positive electrode active material precursor, wherein the first positive electrode active material precursor has a face-centered cubic crystal structure.
[0038] (4) In any one of the above (1) to (3), the present invention provides a cathode active material precursor, wherein the second cathode active material precursor is in the form of secondary particles, single particles or amorphous.
[0039] (5) In any one of the above (1) to (4), the present invention provides a cathode active material precursor, wherein the second cathode active material precursor has an average particle size (D 50 ).
[0040] (6) In any one of the above (1) to (5), the present invention provides a cathode active material precursor, wherein the third cathode active material precursor is in a secondary particle form, a single particle form, or an amorphous shape.
[0041] (7) In any one of the above (1) to (6), the present invention provides a positive electrode active material precursor, wherein the third positive electrode active material precursor has an average particle size (D 50 ).
[0042] (8) In any one of the above (1) to (7), the present invention provides a positive electrode active material precursor, wherein based on 100 parts by weight of the first positive electrode active material precursor, the positive electrode active material precursor contains one or more selected from the second positive electrode active material precursor and the third positive electrode active material precursor in an amount of 0.5 parts by weight to 5 parts by weight.
[0043] (9) The present invention provides a method for preparing a positive electrode active material, the method comprising the following steps:
[0044] The cathode active material precursor according to any one of (1) to (8) is mixed with a lithium-containing raw material, and the mixture is then fired at a temperature of 700° C. to less than 830° C. to obtain a lithium transition metal oxide in the form of single particles.
[0045] (10) The present invention provides a positive electrode active material in the form of a single particle, the positive electrode active material in the form of a single particle being prepared by the preparation method according to the above (9) and having an average particle size (D 50 ).
[0046] (11) In the above (10), the present invention provides a positive electrode active material in a single particle form, wherein the positive electrode active material in a single particle form has an average particle size (D 50 ).
[0047] Beneficial Effects
[0048] According to the positive electrode active material precursor of the present invention, a mixture of a first positive electrode active material precursor containing a composite transition metal in the form of a single particle and a second positive electrode active material precursor and / or a third positive electrode active material precursor is used, so that even when the positive electrode active material precursor is fired at a relatively lower temperature than the temperature generally required to form single particles when preparing the positive electrode active material, a single particle form of positive electrode active material can be obtained.
[0049] When the cathode active material prepared by the method for preparing a cathode active material according to the present invention is applied to a secondary battery, excellent capacity characteristics, life characteristics, resistance characteristics, and a significant gas generation reduction effect may be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 is a SEM image of the first positive electrode active material precursor used in Example 1.
[0051] Figure 2 This is a SEM image of the nickel-cobalt-manganese hydroxide used in Comparative Example 1.
[0052] Figure 3 This is a SEM image of the nickel-cobalt-manganese oxide used in Comparative Example 2.
[0053] Figure 4 3 is a volume cumulative particle size diagram of the positive electrode active materials prepared in Example 1 and Comparative Examples 1 and 2.
[0054] Figure 5 are SEM images of the positive electrode active materials prepared in (A) Example 1, (B) Comparative Example 1, and (C) Comparative Example 2.
[0055] Figure 61 is the XRD data of the positive electrode active materials prepared in Example 1 and Comparative Example 1.
[0056] Figure 7 1 is the XRD data of the first positive electrode active material precursor and the third positive electrode active material precursor used in Example 1.
[0057] Figure 8 1 is the EDS data of the first positive electrode active material precursor used in Example 1. DETAILED DESCRIPTION
[0058] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should also be understood that based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant field and the technical concept of the present invention.
[0059] In the present specification, it should be understood that the terms "include", "comprises" or "has" are intended to specify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.
[0060] In this specification, the average particle size (D 50 ) refers to the particle size at which 50% of the volume cumulative particle size distribution of the positive electrode active material precursor or the positive electrode active material or the lithium transition metal oxide powder is obtained. Average particle size (D 50 ) can be measured by laser diffraction. For example, the average particle size (D 50 ) can be measured by the following steps: dispersing the positive electrode active material powder in a dispersion medium, and then introducing the mixture into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) to irradiate with ultrasonic waves of about 28 kHz to an output of 60 W, thereby obtaining a volume cumulative particle size distribution diagram, and then obtaining the particle size corresponding to 50% of the volume cumulative amount.
[0061] In the present specification, the term “on” includes not only the case in which a certain constituent element is directly formed on the upper surface of another constituent element but also the case in which a third constituent element is interposed therebetween.
[0062] In the present specification, the single particle form is a concept in contrast to the spherical secondary particle form prepared by conventional methods and formed by agglomeration of tens to hundreds of primary particles, which is a form in which each particle is separated and / or dispersed from each other to form an independent and / or separate phase, but may also include a form in which two to ten particles or two to five particles are attached to each other, etc.
[0063] The present invention will be described in detail below.
[0064] Positive electrode active material precursor
[0065] The precursor of the positive electrode active material according to the present invention includes:
[0066] a first positive electrode active material precursor having a composition represented by the following Chemical Formula 1 and including a composite transition metal in the form of single particles, and
[0067] one or more selected from a second positive electrode active material precursor having a composition represented by the following Chemical Formula 2 and a third positive electrode active material precursor having a composition represented by the following Chemical Formula 3.
[0068] [Chemical Formula 1]
[0069] Ni a1 M 1 b1 Mn c1 M 2 d1
[0070] In the above Chemical Formula 1,
[0071] M 1 is one or more selected from Co and Al,
[0072] M 2 is one or more selected from Nb, Ti, Mg, Ta, Zr, Ca, Mo, V, Y, W, and Sc, and
[0073] 0.6 ≤ a1 < 1, 0 < b1 ≤ 0.4, 0 ≤ c1 ≤ 0.4, 0 ≤ d1 ≤ 0.2, and
[0074] [Chemical Formula 2]
[0075] M 3 a2 M 4 b2 (OH) c2
[0076] In the above Chemical Formula 2,
[0077] M 3 is one or more selected from Ni, Co, Mn, Al, and Zr,
[0078] M 4 is one or more selected from Nb, Ti, Mg, Ta, Ca, Mo, V, Y, W, and Sc, and
[0079] 0 < a2 ≤ 1, 0 ≤ b2 < 1, 2 ≤ c2 ≤ 4, and
[0080] [Chemical formula 3]
[0081] M 5 a3 M 6 b3 O c3
[0082] In the above chemical formula 3,
[0083] M 5 is one or more selected from Ni, Co, Mn, Al and Zr,
[0084] M 6 is one or more selected from Nb, Ti, Mg, Ta, Ca, Mo, V, Y, W and Sc, and
[0085] 0 <a3≤3,0≤b3<3,1≤c3≤4。
[0086] The present inventors have repeatedly studied on developing a positive electrode active material capable of achieving excellent life characteristics and resistance characteristics, and have found that when a first positive electrode active material precursor of a composite transition metal in the form of a single particle is mixed with a transition metal hydroxide and / or a transition metal oxide and used as a positive electrode active material precursor, even when the positive electrode active material precursor is fired at a relatively low temperature, a positive electrode active material with a high degree of single particleization capable of achieving excellent life characteristics and resistance characteristics can be prepared, and the present invention has been completed.
[0087] First, when a conventional positive electrode active material precursor having a secondary particle form formed by agglomeration of primary particles is used, high temperature firing of 830° C. or higher is required to prepare a positive electrode active material in a single particle form, but when a positive electrode active material precursor containing a first positive electrode active material precursor as a composite transition metal in a single particle form and a transition metal hydroxide (a second positive electrode active material precursor) and / or a transition metal oxide (a third positive electrode active material precursor) is used as in the present invention, there is an advantage in that a positive electrode active material in a single particle form can be prepared even by firing at a temperature lower than 830° C. Therefore, a phase transition to a rock salt structure of a NiO phase, which may occur when high temperature firing of 830° C. or higher is performed, does not occur, and a positive electrode active material having excellent performance can be prepared.
[0088] Furthermore, the cathode active material precursor according to the present invention contains an isotropic composite transition metal, and thus is easily formed into a single particle because the particles grow uniformly regardless of the growth direction.
[0089] According to the present invention, the first positive electrode active material precursor may be the composite transition metal itself in the form of single particles having the composition represented by Chemical Formula 1 above. On the other hand, the first positive electrode active material precursor may be a precursor in which the surface of the composite transition metal in the form of single particles having the composition represented by Chemical Formula 1 below reacts with oxygen or moisture in the atmosphere and is surface-modified with an oxide or hydrate.
[0090] In Chemical Formula 1 above,
[0091] a1 represents the atomic fraction of nickel among the metal elements in the first positive electrode active material precursor, and may satisfy 0.6 ≤ a1 < 1, 0.6 ≤ a1 ≤ 0.98, or 0.7 ≤ a1 ≤ 0.95.
[0092] b1 represents the atomic fraction of M 1 element among the metal elements in the first positive electrode active material precursor, and may satisfy 0 < b1 ≤ 0.4, 0.01 ≤ b1 ≤ 0.4, or 0.01 ≤ b1 ≤ 0.3.
[0093] c1 represents the atomic fraction of manganese among the metal elements in the first positive electrode active material precursor, and may satisfy 0 ≤ c1 ≤ 0.4, 0.01 ≤ c1 ≤ 0.4, or 0.01 ≤ c1 ≤ 0.3, and
[0094] d1 represents the atomic fraction of M 2 element among the metal elements in the first positive electrode active material precursor, and may satisfy 0 < d1 ≤ 0.4, 0 ≤ d1 ≤ 0.4, or 0 ≤ d1 ≤ 0.05.
[0095] In terms of improving the resistance characteristics of the battery, the first positive electrode active material precursor may contain nickel and cobalt. For example, the first positive electrode active material precursor may have the composition represented by Chemical Formula 1-1 below.
[0096] [Chemical Formula 1-1]
[0097] Ni a1 Co x1 Al y1 Mn c1 M 2 d1
[0098] In Chemical Formula 1-1 above,
[0099] M 2 is one or more selected from Nb, Ti, Mg, Ta, Zr, W, and Sc, and
[0100] 0.6 ≤ a1 < 1, 0 < x1 ≤ 0.4, 0 ≤ y1 ≤ 0.4, 0 ≤ c1 ≤ 0.4, 0 ≤ d1 ≤ 0.2.
[0101] On the other hand, the first positive electrode active material precursor may be a composite transition metal itself in the form of a single particle having a composition represented by the following Chemical Formula 1. In addition, the first positive electrode active material precursor may be one in which the surface of the composite transition metal in the form of a single particle having a composition represented by the following Chemical Formula 1 reacts with oxygen or moisture in the atmosphere and is surface-modified with an oxide or a hydrate.
[0102] According to the present invention, the first positive active material precursor may have an average particle size (D 50 Specifically, the first positive active material precursor may have an average particle size (D 50 When the average particle size of the first positive electrode active material precursor is within the above range, the number of lithium paths in contact with the electrolyte increases, resulting in an increase in the number of lithium ions that can be reversibly used, so that high capacity and output characteristics can be exhibited.
[0103] According to the present invention, the first positive active material precursor may have a face-centered cubic structure. When the crystal structure of the first positive active material precursor has a face-centered cubic structure, due to the properties of the close-packed face-centered cubic structure, a large amount of positive active material can be prepared with a small volume and weight of the precursor, so that processability can be improved.
[0104] In terms of improving the low reactivity of the first positive electrode active material precursor, the second positive electrode active material precursor may be Ni(OH)2, Co(OH)2, Zr(OH)4, Al(OH)3 or a combination thereof.
[0105] According to the present invention, the second positive active material precursor may be in the form of secondary particles, in the form of single particles, or in an amorphous shape.
[0106] According to the present invention, the second positive active material precursor may have an average particle size (D 50 Specifically, the second positive electrode active material precursor may have an average particle size (D 50 ). When the average particle size of the second positive electrode active material precursor is within the above range, the reactivity with the first positive electrode active material precursor can be maximized.
[0107] In terms of improving the low reactivity of the first positive electrode active material precursor, the third positive electrode active material precursor may specifically be NiO, Co3O4, MnO2, ZrO2, Al3O3 or a combination thereof.
[0108] According to the present invention, the third positive active material precursor may be in the form of secondary particles, in the form of single particles, or in an amorphous shape.
[0109] According to the present invention, the third positive active material precursor may have an average particle size (D 50 Specifically, the third positive electrode active material precursor may have an average particle size (D 50 ). When the average particle size of the third positive electrode active material precursor is within the above range, the reactivity with the first positive electrode active material precursor can be maximized.
[0110] According to the present invention, the cathode active material precursor may include one or more selected from the second cathode active material precursor and the third cathode active material precursor in an amount of 0.5 to 5 parts by weight based on 100 parts by weight of the first cathode active material precursor.
[0111] Method for preparing positive electrode active material
[0112] The method for preparing a positive electrode active material according to the present invention comprises the steps of mixing a positive electrode active material precursor according to the present invention with a raw material containing lithium, and then firing the mixture at a temperature of 700° C. to less than 830° C., thereby obtaining a lithium transition metal oxide in the form of a single particle. The method for preparing a positive electrode active material can prepare a positive electrode active material doped with a doping element by mixing and firing a raw material containing a doping element when mixing the positive electrode active material precursor and the raw material containing lithium. In addition, the method for preparing a positive electrode active material can prepare a positive electrode active material as follows: wherein a coating is formed on the lithium transition metal oxide by mixing the prepared lithium transition metal oxide in the form of a single particle with a raw material containing a coating element and heat-treating the mixture.
[0113] In the method of preparing a positive electrode active material using a conventional positive electrode active material precursor, high temperature firing of 830°C or more is required to obtain a positive electrode active material in the form of a single particle. However, according to the present invention, since a positive electrode active material precursor containing a first positive electrode active material precursor as a composite transition metal in the form of a single particle and a transition metal hydroxide (a second positive electrode active material precursor) and / or a transition metal oxide (a third positive electrode active material precursor) is used in the preparation of the positive electrode active material, even when the positive electrode active material precursor is fired at a low temperature of 700°C to less than 830°C, a positive electrode active material in the form of a single particle can be obtained. That is, even when the positive electrode active material precursor is fired at a relatively low temperature of 700°C to less than 830°C instead of being fired at a high temperature of 830°C or more, a positive electrode active material in the form of a single particle can be obtained.
[0114] The method for preparing a positive electrode active material according to the present invention may include: mixing a positive electrode active material precursor according to the present invention, a raw material containing lithium, and optionally further mixing a raw material containing a doping element, etc., and then firing the mixture once at a temperature of 700° C. to less than 830° C. to obtain a first fired product; and mixing the first fired product, a raw material containing lithium, and optionally further mixing a raw material containing a doping element, etc., and then firing the mixture twice at a temperature of 700° C. to 800° C. to obtain a second fired product. When firing is performed in two stages, a region in which crystallinity is deteriorated due to high-temperature firing during the primary firing can be restored in the secondary firing.
[0115] The method for preparing a positive electrode active material may further include mixing the second fired product and a raw material containing a coating element, and then heat-treating the mixture at a temperature of 500° C. to 750° C. to form a coating layer on the lithium transition metal oxide in the form of a single particle. When the method for preparing a positive electrode active material further includes forming a coating layer, there is an advantage in that a deteriorated surface can be further improved.
[0116] The lithium-containing raw material may include one or more selected from lithium hydroxide hydrate, lithium carbonate, lithium nitrate and lithium oxide. The lithium-containing raw material may specifically be lithium hydroxide hydrate, more specifically LiOH·H2O. In this case, the reactivity between the precursor having a high nickel atomic fraction in the metal element in the precursor and the lithium-containing raw material can be improved.
[0117] When preparing the positive electrode active material, the positive electrode active material precursor may be mixed with the lithium-containing raw material so that the molar ratio (M:Li) of the transition metal M (e.g., Ni+Co+Al and Ni+Co+Mn+Al) contained in the positive electrode active material precursor to the lithium (Li) contained in the lithium-containing raw material is 1:1.02 to 1:1.2, specifically 1:1.02 to 1:1.1, and more specifically 1:1.02 to 1:1.07. In this case, the capacity of the prepared positive electrode active material is improved, and unreacted Li does not remain as a by-product, so that separation of the positive electrode active material particles (which causes agglomeration of the positive electrode active material) may not occur after firing.
[0118] When the firing is performed in two stages as described above, in the first firing step, the positive electrode active material precursor may be mixed with the lithium-containing raw material so that the molar ratio (M:Li) of the transition metal M (e.g., Ni+Co+Al and Ni+Co+Mn+Al) contained in the positive electrode active material precursor to the lithium (Li) contained in the lithium-containing raw material is 1:0.9 to 1:1.2, specifically 1:0.95 to 1:1.1, more specifically 1:0.98 to 1:1.02. In addition, in the second firing step, the first fired product may be mixed with the lithium-containing raw material so that the molar ratio of the transition metal contained in the first fired product to the lithium contained in the lithium-containing raw material is 1:0.01 to 1:0.07, more specifically 1:0.03 to 1:0.05.
[0119] The firing temperature may be 700°C to less than 830°C. Specifically, the firing temperature may be 700°C, 720°C, 750°C or more, equal to or less than 820°C, or less than 830°C. When the firing temperature is within the above range, the crystallinity of the particles can be increased, and the Ni 2+ The phenomenon that ions enter the Li layer can improve the conductivity of lithium ions. Therefore, when applied to batteries, excellent electrochemical characteristics can be achieved.
[0120] The firing may be performed in an oxygen atmosphere. In this case, the crystallinity of the positive electrode active material can be increased by increasing reactivity, firing particles uniformly, and preventing nickel reduction, thereby maintaining Ni well. 3+ , which is conducive to the formation of R-3m layered structure during the firing interval.
[0121] The firing can be performed for 5 to 20 hours. Specifically, the firing can be performed for 8 hours, 10 hours, 15 hours or more, 16 hours or less than 20 hours. When the firing duration is within the above range, the effect is that the lithium source reacts for a sufficient period of time, thereby increasing the crystallinity by rearrangement of atoms, and reducing the internal defects of the single particle.
[0122] The positive electrode active material prepared by the method of preparing a positive electrode active material is a lithium transition metal oxide in a single particle form, and may have a composition represented by Chemical Formula 4 below.
[0123] [Chemical formula 4]
[0124] Li x [Ni a4 M 1 b4 Mn c4 M 7 d4 ]O 2-y A y
[0125] In the above Chemical Formula 4,
[0126] M 1 is one or more selected from Co and Al,
[0127] M 7 is one or more selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, Sc and W,
[0128] A is one or more selected from F, Cl, Br, I, At and S, and
[0129] 0.9 ≤ x ≤ 1.2, 0.6 ≤ a4 < 1, 0 < b4 ≤ 0.4, 0 ≤ c4 ≤ 0.4, 0 ≤ d4 ≤ 0.2, a4 + b4 + c4 + d4 = 1, 0 ≤ y ≤ 0.2.
[0130] a4 represents the atomic fraction of nickel among the metal elements other than lithium in the positive electrode active material, and can satisfy 0.6 ≤ a4 < 1, 0.6 ≤ a4 ≤ 0.98 or 0.7 ≤ a4 ≤ 0.95.
[0131] b4 represents the atomic fraction of the M 1 element among the metal elements other than lithium in the positive electrode active material, and can satisfy 0 < b4 ≤ 0.4, 0.01 ≤ b4 ≤ 0.4 or 0.01 ≤ b4 ≤ 0.3.
[0132] c4 represents the atomic fraction of manganese among the metal elements other than lithium in the positive electrode active material, and can satisfy 0 ≤ c4 ≤ 0.4, 0.01 ≤ c4 ≤ 0.4 or 0.01 ≤ c4 ≤ 0.3.
[0133] d4 represents the atomic fraction of the M 7 element among the metal elements other than lithium in the positive electrode active material, and can satisfy 0 ≤ d4 ≤ 0.2, 0 ≤ d4 ≤ 0.1 or 0 ≤ d4 ≤ 0.05.
[0134] According to the present invention, the positive electrode active material may contain nickel and cobalt. For example, the positive electrode active material may have a composition represented by the following Chemical Formula 4-1.
[0135] [Chemical Formula 4-1]
[0136] Li x [Ni a4 Co x' Al y' Mn c4 M 7 d4 O 2-y A y
[0137] In the above Chemical Formula 4-1,
[0138] M 7 is one or more selected from B, Mg, Ca, Ti, V, Cr, Fe, Zn, Ga, Y, Zr, Nb, Mo, Ta, Sc and W,
[0139] A is one or more selected from F, Cl, Br, I, At and S, and
[0140] 0.9≤x≤1.2,0.6≤a4<1,0 <x'≤0.4,0≤y'≤0.4,0≤c4≤0.4,0≤d4≤0.2,a4+x'+y'+c4+d4=1,0≤y≤0.2。
[0141] According to the present invention, the positive electrode active material prepared according to the method for preparing a positive electrode active material may have an average particle size (D 50 ) is a single particle positive electrode active material in the form of 3 μm to 12 μm. Specifically, the positive electrode active material prepared according to the method for preparing the positive electrode active material may have an average particle size (D) of 3 μm, 4 μm, 5 μm or more, 8 μm, 10 μm or less, or 12 μm or less. 50 ). In this case, the electrochemical characteristics of a battery including the positive electrode active material can be improved.
[0142] On the other hand, when lithium transition metal oxides contain + ) transition metal cations, a phenomenon occurs in which the transition metal cations are incorporated into the lithium layer, which is called a cation mixing phenomenon. In the case of lithium nickel cobalt oxides, since ions such as Ni 3+ 、Co 3+ Same size as Li + However, in nickel ions, Ni with an oxidation number of +2 2+ ions are similar in size to lithium ions, allowing cation mixing to occur easily. 2+ When ions are mixed in the lithium layer, the layered crystal structure is not properly developed, so that the structural stability of the active material is deteriorated, and the migration of lithium ions is restricted by Ni 2+Ion suppression reduces battery performance. In particular, when the positive electrode active material precursor is fired at a high temperature of more than 830°C, the proportion of phase transition from the layered structure of stable LiNO2 to the NiO phase increases, and the degree of cation mixing tends to increase significantly. However, the positive electrode active material prepared by the method for preparing a positive electrode active material according to the present invention can be fired at a temperature below 830°C to form a single particle, and at the same time suppress the above-mentioned phase change, so that a positive electrode active material with a high degree of single particleization, a low degree of cation mixing and a high degree of crystallinity can be obtained. Specifically, the degree of cation mixing may be equal to or less than 1%. Therefore, a battery containing a positive electrode active material prepared according to the method for preparing a positive electrode active material can achieve excellent electrochemical performance.
[0143] positive electrode
[0144] Furthermore, the present invention may provide a positive electrode for a lithium secondary battery, the positive electrode comprising the positive electrode active material prepared by the above method.
[0145] Specifically, the positive electrode includes a positive electrode collector and a positive electrode active material layer formed on at least one surface of the positive electrode collector and including the above-mentioned positive electrode active material.
[0146] There is no particular limitation on the positive electrode current collector as long as it has conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can generally have a thickness of 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foamed body, a non-woven fabric body, etc.
[0147] The positive electrode active material layer may include a conductive material and a binder as well as a positive electrode active material.
[0148] The positive electrode active material may be contained in an amount of 80 to 99 wt %, more specifically 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When included within the above content range, excellent capacity characteristics may be exhibited.
[0149] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used without particular limitation, as long as it has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples thereof may include graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used. The content of the conductive material may be 1% to 30% by weight based on the total weight of the positive electrode active material layer.
[0150] Binder is used to improve the bonding between positive active material particles and the adhesion between positive active material and collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used. Based on the gross weight of the positive active material layer, the content of the binder may be 1% to 30% by weight.
[0151] In addition to using the above-mentioned positive electrode active material, the positive electrode can be manufactured according to a conventional method for manufacturing a positive electrode. Specifically, the positive electrode active material layer-forming composition prepared by dissolving or dispersing the above-mentioned positive electrode active material and a selective binder and a conductive material in a solvent can be coated on a positive electrode collector, followed by drying and rolling to manufacture the positive electrode. At this time, the type and content of the positive electrode active material, binder and conductive material are as described above.
[0152] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc. Any one thereof or a mixture of two or more thereof may be used. If the coating thickness and the preparation yield of the active material layer-forming composition are taken into account, the solvent dissolves or disperses the positive electrode active material, the conductive material, and the binder, and thereafter makes the composition have a viscosity that can show excellent thickness uniformity when used to manufacture the positive electrode, then the amount of the solvent used is sufficient.
[0153] Furthermore, in another method, the positive electrode may be manufactured by casting the positive electrode active material layer-forming composition on a separate support and then laminating a film obtained by peeling off from the support on a positive electrode current collector.
[0154] Lithium secondary battery
[0155] In addition, the present invention can manufacture an electrochemical device including a positive electrode. Specifically, the electrochemical device can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.
[0156] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode positioned opposite to the positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, and since the positive electrode is the same as above, its detailed description will be omitted, and hereinafter, only the remaining components will be described in detail.
[0157] In addition, the lithium secondary battery may selectively further include a battery case accommodating an electrode assembly consisting of a positive electrode, a negative electrode, and a separator, and a sealing member sealing the battery case.
[0158] In the above lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0159] There is no particular restriction on the negative electrode collector as long as it has high conductivity without causing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode collector can generally have a thickness of 3 μm to 500 μm, and as in the case of the positive electrode collector, fine concavoconvexities can be formed on the surface of the negative electrode collector to improve the adhesion of the negative electrode active material. For example, the negative electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0160] The negative electrode active material layer selectively contains a binder and a conductive material in addition to the negative electrode active material.
[0161] As the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples thereof may include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber or amorphous carbon; (semi)metallic materials that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; (semi)metallic oxides capable of doping and dedoping lithium, such as SiO β(0<β<2), SnO2, vanadium oxide or lithium vanadium oxide; or a composite material comprising a (semi)metallic material and a carbonaceous material, such as a Si-C composite material or a Sn-C composite material, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon, high-crystalline carbon, etc. can be used as carbon materials. Representative examples of low-crystalline carbon may include soft carbon and hard carbon, and representative examples of high-crystalline carbon may include irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.
[0162] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.
[0163] The binder is a component that assists the bonding between the conductive material, the active material and the current collector, and is generally added in an amount of 0.1% to 10% by weight based on the total weight of the negative electrode active material layer. Examples of binders may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, various copolymers thereof, and the like.
[0164] The conductive material is a component that further improves the conductivity of the negative electrode active material, and the amount added may be 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. There is no particular limitation on the conductive material as long as it has conductivity without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc. may be used.
[0165] The negative electrode active material layer can be prepared by coating a negative electrode active material layer-forming composition prepared by dissolving or dispersing the negative electrode active material and a selective binder and a conductive material in a solvent on a negative electrode collector, followed by drying; or it can be prepared by casting the negative electrode active material layer-forming composition on a separate carrier and then stacking the film peeled off from the carrier on the negative electrode collector.
[0166] On the other hand, in the above-mentioned lithium secondary battery, the diaphragm is used to separate the negative electrode and the positive electrode and provide a mobile path for lithium ions, and any diaphragm commonly used as a diaphragm in a lithium secondary battery can be used without particular restrictions, in particular, a diaphragm having a high water retention capacity for the electrolyte and low resistance to the movement of electrolyte ions is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure with more than two layers thereof. In addition, conventional porous nonwoven fabrics can be used, for example, nonwoven fabrics formed by glass fibers, polyethylene terephthalate fibers, etc. with a high melting point. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a monolayer or multilayer structure.
[0167] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used to manufacture a lithium secondary battery, but is not limited thereto.
[0168] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0169] As the organic solvent, any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among the above solvents, carbonate solvents are preferred, and more preferably a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) which can improve the charge / discharge performance of the battery. In this case, when the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be shown to be excellent.
[0170] As a lithium salt, any compound can be used without particular limitation, as long as it can provide lithium ions used in lithium secondary batteries. Specifically, as a lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The lithium salt can be used in a concentration range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent performance, and lithium ions can be effectively moved.
[0171] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, the electrolyte may further contain one or more types of additives, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride, etc. At this time, the content of the additive may be 0.1 wt % to 5 wt % based on the total weight of the electrolyte.
[0172] A lithium secondary battery comprising the positive electrode active material according to the present invention as described above stably exhibits excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in the fields of portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0173] Therefore, a battery module including a lithium secondary battery as a unit cell and a battery pack including the battery module are provided.
[0174] The battery module or battery pack can be used as a power source for one or more medium to large devices such as: power tools, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV), or power storage systems.
[0175] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may have a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0176] The lithium secondary battery according to the present invention can be used in a battery cell used as a power source for a small device, and can also be preferably used as a unit battery in a medium or large battery module including a plurality of battery cells.
[0177] Preferred Embodiments
[0178] Hereinafter, the embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments set forth herein.
[0179] Examples and Comparative Examples
[0180] Example 1
[0181] Preparation contains 80g of Ni 0.96 Co 0.04 A positive electrode active material precursor of a composition of a single particle form of nickel-cobalt alloy (Avention Co., Ltd.) (a first positive electrode active material precursor), 0.557 g of Al(OH)3 (DAEJOO KCCo., Ltd.) (a second positive electrode active material precursor) and 0.162 g of ZrO2 (Guangdong Orient Zirconic Ind Sci&Tech Co., Ltd.) (a third positive electrode active material precursor), 0.102 g of Y2O3 and 59.89 g of LiOH·H2O, are mixed so that the molar ratio of Ni+Co+Al:Li is 1:1, and the mixture is heated from room temperature to 810°C at a heating rate of 5°C / min, and then fired once at 810°C for 6 hours to obtain a first fired product.
[0182] 100 g of the first fired product, 0.479 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 1.730 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Al:Li was 1:0.04, and the mixture was heated from room temperature to 760°C at a heating rate of 5°C / min, and then secondary fired at 760°C for 9 hours to obtain a second fired product.
[0183] 100 g of the secondary fired product, 1.940 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 0.145 g of Al(OH)3 (DAEJOO KC Co., Ltd.) were mixed, and the mixture was heated from room temperature to 700°C at a heating rate of 5°C / min, heat-treated at 700°C for 3 hours, and then heat-treated for 3 hours by lowering the temperature to 500°C to prepare a lithium transition metal oxide (Li[Ni 0.931 Co 0.060 Al 0.007 Zr 0.001 Y 0.001 ]O2).
[0184] For reference, Figure 1 It shows that the Ni 0.96 Co 0.04 The composition of the first positive electrode active material precursor is shown in Figure 1 and is a SEM image of a nickel-cobalt alloy (Avention Co., Ltd.) in a single particle form. The average particle size (D 50 ) is 3.09μm.
[0185] Example 2
[0186] Preparation contains 80g of Ni 0.96 Co 0.04 A positive electrode active material precursor of a composition and being a single particle form of nickel-cobalt alloy (Avention Co., Ltd.) (a first positive electrode active material precursor) and 0.557 g of Al(OH)3 (DAEJOO KCCo., Ltd.) in an amorphous powder state (a second positive electrode active material precursor), and 59.89 g of LiOH·H2O, are mixed so that the molar ratio of Ni+Co+Al:Li is 1:1, and the mixture is heated from room temperature to 810°C at a heating rate of 5°C / min, and then fired once at 810°C for 6 hours to obtain a first fired product.
[0187] 100 g of the first fired product and 1.730 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Al:Li was 1:0.04, and the mixture was heated from room temperature to 760°C at a heating rate of 5°C / min, and then secondary fired at 760°C for 9 hours to obtain a second fired product.
[0188] 100 g of the secondary fired product, 1.940 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 0.145 g of Al(OH)3 (DAEJOO KC Co., Ltd.) were mixed, and the mixture was heated from room temperature to 700°C at a heating rate of 5°C / min, a primary heat treatment was performed at 700°C for 3 hours, and then a secondary heat treatment was performed by lowering the temperature to 500°C for 3 hours to prepare a lithium transition metal oxide (Li[Ni 0.937 Co 0.056 Al 0.007 ]O2).
[0189] Example 3
[0190] Preparation contains 80g of Ni 0.96 Co 0.04 A positive electrode active material precursor of a composition and being a single particle form of nickel-cobalt alloy (Avention Co., Ltd.) (a first positive electrode active material precursor) and 0.557 g of Al(OH)3 (DAEJOO KCCo., Ltd.) in an amorphous powder state (a second positive electrode active material precursor), and 59.89 g of LiOH·H2O, are mixed so that the molar ratio of Ni+Co+Al:Li is 1:1, and the mixture is heated from room temperature to 810°C at a heating rate of 5°C / min, and then fired once at 810°C for 6 hours to obtain a first fired product.
[0191] 100 g of the first fired product, 0.479 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 1.730 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Al:Li was 1:0.04, and the mixture was heated from room temperature to 760°C at a heating rate of 5°C / min, and then secondary fired at 760°C for 9 hours to obtain a second fired product.
[0192] 100 g of the secondary fired product, 1.940 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 0.145 g of Al(OH)3 (DAEJOO KC Co., Ltd.) were mixed, and the mixture was heated from room temperature to 700°C at a heating rate of 5°C / min, a primary heat treatment was performed at 700°C for 3 hours, and then a secondary heat treatment was performed by lowering the temperature to 500°C for 3 hours to prepare a lithium transition metal oxide (Li[Ni 0.933 Co 0.060 Al 0.007 ]O2).
[0193] Comparative Example 1
[0194] 100 g of spherical nickel cobalt manganese hydroxide having a Ni:Co:Mn molar ratio of 95:3:2 (Huajin Co., Ltd.), 0.424 g of Al(OH)3 in an amorphous powder state (DAEJOO KC Co., Ltd.) and 0.203 g of ZrO2 in an amorphous powder state (Guangdong Orient Zirconic Ind Sci&Tech Co., Ltd.), 0.127 g of Y2O3 and 45.52 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Mn+Al:Li was 1:1, and the mixture was heated from room temperature to 830°C at a heating rate of 5°C / min, and then fired once at 830°C for 6 hours to obtain a first fired product.
[0195] 100 g of the first fired product and 2.146 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Mn+Al:Li was 1:0.05, and the mixture was heated from room temperature to 760°C at a heating rate of 5°C / min, and then secondary fired at 760°C for 9 hours to obtain a second fired product.
[0196] 100 g of the secondary fired product, 1.940 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 0.145 g of Al(OH)3 (DAEJOO KC Co., Ltd.) were mixed, and the mixture was heated from room temperature to 700°C at a heating rate of 5°C / min, a primary heat treatment was performed at 700°C for 3 hours, and then a secondary heat treatment was performed by lowering the temperature to 500°C for 3 hours to prepare a lithium transition metal oxide (Li[Ni 0.923 Co 0.049 Mn 0.019 Al 0.007 Zr 0.001 Y 0.001 ]O2).
[0197] For reference, Figure 2 The SEM image of spherical nickel cobalt manganese hydroxide (Huajin Co., Ltd.) having a Ni:Co:Mn molar ratio of 95:3:2 is shown. The average particle size (D 50 ) is 3.5μm.
[0198] Comparative Example 2
[0199] 100 g of spherical nickel cobalt manganese oxide (LG Chemical Co., Ltd.) having a Ni:Co:Mn molar ratio of 96:3:1, 0.526 g of Al(OH)3 (DAEJOO KC Co., Ltd.) in an amorphous powder state and 0.203 g of ZrO2 in an amorphous powder state (Guangdong Orient Zirconic Ind Sci&Tech Co., Ltd.), 0.127 g of Y2O3 and 56.486 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Mn+Al:Li was 1:1, and the mixture was heated from room temperature to 830°C at a heating rate of 5°C / min, and then fired once at 830°C for 12 hours to obtain a first fired product.
[0200] 100 g of the first fired product, 0.479 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 1.730 g of LiOH·H2O were prepared and mixed so that the molar ratio of Ni+Co+Mn+Al:Li was 1:0.04, and the mixture was heated from room temperature to 760°C at a heating rate of 5°C / min, and then secondary fired at 760°C for 12 h to obtain a second fired product.
[0201] 100 g of the secondary fired product, 1.940 g of Co(OH)2 (Huayou Cobalt Co., Ltd.) and 0.145 g of Al(OH)3 (DAEJOO KC Co., Ltd.) were mixed, and the mixture was heated from room temperature to 700°C at a heating rate of 5°C / min, a primary heat treatment was performed at 700°C for 3 hours, and then a secondary heat treatment was performed by lowering the temperature to 500°C for 3 hours to prepare a lithium transition metal oxide (Li[Ni 0.932 Co 0.049 Mn 0.01 Al 0.007 Zr 0.001 Y 0.001 ]O2).
[0202] For reference, Figure 3 The SEM image of spherical nickel cobalt manganese oxide (Avention Co., Ltd.) having a Ni:Co:Mn molar ratio of 96:3:1 is shown. The average particle size (D 50 ) is 5.18μm.
[0203] Experimental example
[0204] Experimental Example 1: Analysis of positive electrode active material precursor and positive electrode active material
[0205] The volume cumulative particle size diagram of the first positive electrode active material precursor used in Examples 1 to 3, the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 and 2 was obtained using a particle size measuring device (Microtrac Co., Ltd. S3500, diffraction index = 1.55), and the D 最小 , D 50 , D 最大 The values are shown in Table 1 below. Figure 4 3 is a volume cumulative particle size diagram of the positive electrode active materials prepared in Example 1 and Comparative Examples 1 and 2.
[0206] In addition, SEM images of the positive electrode active materials prepared in Example 1 and Comparative Examples 1 and 2 were measured using a scanning electron microscope (JEOL Co., Ltd.) and are shown in FIG. Figure 5 middle. Specifically, Figure 5 (A) is a SEM image of the positive electrode active material prepared in Example 1, Figure 5 (B) is a SEM image of the positive electrode active material prepared in Comparative Example 1, Figure 5 (C) is a SEM image of the positive electrode active material prepared in Comparative Example 2.
[0207] In addition, XRD data of the positive electrode active materials prepared in Example 1 and Comparative Example 1 were measured using XRD (Bruker Co., Ltd., D8 Endeavor, Cu target) and are shown in Figure 6 Reference Figure 6 , it can be confirmed that even when the cathode active material precursor of Example 1 was mixed with a lithium-containing raw material and then fired, a layered type cathode active material was prepared.
[0208] In addition, XRD data of the first positive electrode active material precursor and the third positive electrode active material precursor used in Example 1 were measured using XRD (Bruker Co., Ltd., D8 Endeavor, Cu target) and are shown in FIG. Figure 7 Reference Figure 7 It can be confirmed that the first positive electrode active material precursor has a space group of Fm-3M and is therefore FCC (face-centered cubic), and the third positive electrode active material precursor has a space group of Fm-3m and Fd-3m O2 (spinel type) and therefore has a cubic crystal structure.
[0209] In addition, EDS data of the first positive electrode active material precursor used in Example 1 were measured using EDS (ThermoFisher Co., Ltd., Quanta 250 FEG) and are shown in FIG. Figure 8 Reference Figure 8 , it can be confirmed that the alloy precursor of Example 1 is a metal in which Ni and Co are mixed.
[0210]
[0211] Experimental Example 2: Evaluation of Capacity and Resistance Characteristics
[0212] Lithium secondary batteries were manufactured using the positive electrode active materials prepared in Examples and Comparative Examples, respectively, and the initial charge capacity, initial discharge capacity, capacity retention rate, and resistance increase rate of each lithium secondary battery were evaluated.
[0213] The positive electrode active material, conductive material (FX35) and binder (PVdF) prepared in each embodiment and comparative example were mixed in an N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 95:2:3 to prepare a positive electrode slurry. The positive electrode slurry was coated on one surface of an aluminum current collector, dried, and then rolled to produce a positive electrode. The separator was inserted between the positive electrode and the Li metal to produce an electrode assembly, and the electrode assembly was placed inside the battery housing, and then an electrolyte was injected therein to produce a lithium secondary battery. At this time, as an electrolyte, an electrolyte in which 1M LiPF6 was dissolved in an organic solvent in which ethylene carbonate: ethyl methyl carbonate: diethyl carbonate was mixed in a volume ratio of 3:3:4 was used.
[0214] Then, each secondary battery was charged at a constant current of 0.2 C at 25° C. to 4.25 V. Thereafter, discharge was performed at a constant current of 0.2 C to 2.5 V to measure the initial charge capacity and the initial discharge capacity. The results are shown in Table 2 below.
[0215] In addition, the capacity of the lithium secondary battery was measured by repeating a charge and discharge cycle of charging the battery at a constant current of 0.5 C and discharging the battery at a constant current of 1 C at 45° C. for 50 times in the range of 2.5 V to 4.25 V, and specifically, the 50th cycle discharge capacity (C 50 ) and the percentage of the first cycle discharge capacity (C1) (C 50 / C1×100) was set as the capacity retention rate and is shown in the following Table 2. In addition, the DCIR (R 50 ) and the percentage of DCIR(R1) obtained by dividing the voltage drop (ΔV) in the first discharge cycle for 60 seconds by the current (R 50 / R1×100) was set as the resistance increase rate and is shown in the following Table 2.
[0216]
[0217] Refer to Table 1 and Figure 5 It can be confirmed that the positive electrode active material prepared using the positive electrode active material precursor according to the present invention has a large average particle size (D 50 ) and a high degree of single particle formation, therefore, it can be seen that the cathode active material precursor according to the present invention can be usefully used to prepare medium and large-sized single particles. In addition, referring to Table 2, although each cathode active material of Examples 1 to 3 is prepared by firing the precursor at a relatively lower temperature than the case of the cathode active materials of Comparative Examples 1 and 2, it can be confirmed that the single particles are well formed and exhibit a comparable or excellent level of battery performance.
[0218] In summary, the positive electrode active material precursor according to the present invention uses a mixture of a first positive electrode active material precursor containing a composite transition metal in the form of a single particle and a second positive electrode active material precursor and / or a third positive electrode active material precursor, so that it can be seen that even when the positive electrode active material precursor is fired at a relatively lower temperature than the temperature generally required to form a single particle when preparing the positive electrode active material, a single particle form of positive electrode active material can be obtained. In addition, when the positive electrode active material prepared by the method for preparing a positive electrode active material according to the present invention is applied to a secondary battery, it can be seen that excellent capacity characteristics, life characteristics, resistance characteristics and a significant gas generation reduction effect can be achieved.
Claims
1. A positive electrode active material precursor, comprising: a first positive electrode active material precursor having a composition represented by the following Chemical Formula 1 and containing a composite transition metal in a single particle form; and One or more selected from a second positive electrode active material precursor having a composition represented by the following Chemical Formula 2 and a third positive electrode active material precursor having a composition represented by the following Chemical Formula 3: [Chemical formula 1] Ni a1 M 1 b1 Mr c1 M 2 d1 Wherein in the above chemical formula 1, M 1 is one or more selected from Co and Al, M 2 is one or more selected from Nb, Ti, Mg, Ta, Zr, Ca, Mo, V, Y, W and Sc, and 0.6≤a1<1,0 <b1≤0.4,0≤c1≤0.4,0≤d1≤0.2, [Chemical formula 2] M 3 a2 M 4 b2 (OH) c2 Wherein in the above chemical formula 2, M 3 is one or more selected from Ni, Co, Mn, Al and Zr, M 4 is one or more selected from Nb, Ti, Mg, Ta, Ca, Mo, V, Y, W and Sc, and 0 <a2≤1,0≤b2<1,2≤c2≤4, [Chemical formula 3] M 5 a3 M 6 b3 O c3 Wherein in the above chemical formula 3, M 5 is one or more selected from Ni, Co, Mn, Al and Zr, M 6 is one or more selected from Nb, Ti, Mg, Ta, Ca, Mo, V, Y, W and Sc, and 0 <a3≤3,0≤b3<3,1≤c3≤4。 2. The positive electrode active material precursor according to claim 1, wherein the first positive electrode active material precursor has an average particle size (D 50 ). 3 . The positive electrode active material precursor according to claim 1 , wherein the first positive electrode active material precursor has a face-centered cubic crystal structure. 4 . The cathode active material precursor according to claim 1 , wherein the second cathode active material precursor is in a secondary particle form, a single particle form, or is amorphous.
5. The positive electrode active material precursor according to claim 1, wherein the second positive electrode active material precursor has an average particle size (D 50 ). 6 . The cathode active material precursor according to claim 1 , wherein the third cathode active material precursor is in a secondary particle form, a single particle form, or is amorphous.
7. The positive electrode active material precursor according to claim 1, wherein the third positive electrode active material precursor has an average particle size (D 50 ).
8. The positive electrode active material precursor according to claim 1, wherein the positive electrode active material precursor includes one or more selected from the second positive electrode active material precursor and the third positive electrode active material precursor in an amount of 0.5 to 5 parts by weight based on 100 parts by weight of the first positive electrode active material precursor.
9. A method for preparing a positive electrode active material, the method comprising the following steps: The cathode active material precursor according to any one of claims 1 to 8 is mixed with a lithium-containing raw material, and then the mixture is fired at a temperature of 700° C. to less than 830° C., thereby obtaining a lithium transition metal oxide in the form of single particles.
10. A positive electrode active material in the form of a single particle, the positive electrode active material in the form of a single particle being prepared by the preparation method according to claim 9 and having an average particle size (D 50 ).
11. The positive electrode active material according to claim 10, wherein the positive electrode active material has an average particle size (D 50 ) is in the form of single particles of 4 μm to 8 μm.
